Persistence of infectious Enterovirus within free-living amoebae – A novel waterborne risk pathway?. (1st November 2018) - Atanasova, Nikki D.; Dey, Rafik; Scott, Candis; Li, Qiaozhi; Pang, Xiao-Li; Ashbolt, Nicholas J.
Abstract: Free-living amoebae (FLA) are phagocytic protozoa found in natural and engineered water systems. They can form disinfectant-resistant cysts, which can harbor various human pathogenic bacteria, therefore providing them with a means of environmental persistence and dispersion through water distribution and other engineered water systems. The association of FLA with human viruses has been raised, but the limited data on the persistence of infectious virions within amoebae leaves this aspect unresolved. Enteroviruses can cause a wide range of illness and replicate in human respiratory and gastrointestinal tracts, both of which could be exposed through contact with contaminated waters if virus detection and removal are compromised by virion internalization in free-living protozoa. This is especially problematic for high-risk contaminants, such as coxsackieviruses, representative members of the Enterovirus genus that are likely infectious at low doses and cause a variety of symptoms to a vulnerable portion of the population (particularly infants). To investigate Enterovirus persistence within free-living amoebae we co-cultured an infectious clinical coxsackievirus B5 (CVB5) isolate, with the commonly reported tap water amoeba Vermamoeba vermiformis, after which we tracked virus localization and persistence in co-culture over time through a combination of advanced imaging, molecular and cell culture assays. Our results clearly demonstrate that infectious CVB5 can persist in all life stages of the amoebae without causing any visible injury to them. We also demonstrated that the amoeba generated vesicles containing virions that were expelled into the bulk liquid surroundings, a finding previously described for FLA-bacteria interactions, but not for FLA and human pathogenic viruses. Therefore, our findings suggest that the ability of CVB5 to persist in V. vermiformis could be a novel waterborne risk pathway for the persistence and dispersion of infectious human enteric viruses through water systems. Highlights: V. vermiformis grows in cooling towers, hot water tanks and premise plumbing. Coxsackieviruses (CV) are high-risk water contaminants of worldwide prevalence. Persistence of human infectious viruses within amoebae is of public health concern. Infectious virions persisted in amoeba trophozoites, expelled vesicles, cysts. FLA vesicles are a novel means for virion persistence and dispersion.